Indicators and Essay Problem Grids on Three-Dimensional Material: Development of Instruments for Measuring High School Students' Mathematical Problem-Solving Ability - Siti Qomariyah; Rani Darmayanti; Ummi Rosyidah; Irma Ayuwanti (JEMS: Jurnal Edukasi Matematika dan Sains, 2023)
One important component in the education system to measure the success and performance of the learning process is assessment activities. The importance of assessment in the learning process can be used as a benchmark for improving the quality of education. The purpose of this study was to develop a mathematics learning assessment tool to measure high school students' math problem solving abilities. The type of development used is related to the model developed by Thiagaran. The study population consists of five public schools in the city of Pasuruan. The sample of this research was class XII SMA/SMK YALC Pasuruan. The data collection technique uses a description test to solve ten math problems about three-dimensional matter. Data analysis uses validity, reliability, strength, and difficulty. The results of this study indicate that the social essay test instrument measures the mathematical problem-solving abilities of high school students. 9 items are valid and reliable and 1 item is deleted (invalid). Based on the results of this research, we can conclude what is well developed and practical to use